Exploring the material mediation of dialogic space—A qualitative analysis of professional learning in initial teacher education based on reflective sketchbooks. (March 2019) - Moate, Josephine; Hulse, Bethan; Jahnke, Holger; Owens, Allan
Highlights: This study outlines the value of reflective sketchbooks as a forum for fostering different forms of reflection. The importance of vicarious reflection is highlighted in this study. this study suggests a broader conceptualization of dialogic space drawing on the material mediation of reflective practices. This study highlights that value of combining the sensuous and cognive as part of reflective practice. Abstract: This study addresses the crucial relationship between theory and practice as a key feature of professional learning in initial teacher education. The context for the study is an EU-funded intensive programme drawing on different dimensions of insideness and outsideness and arts-based pedagogies in response to the diversity of education today. The data for the study comes from self-selected pages from preservice teacher participants' reflective sketchbooks. As a methodological approach that unifies the sensuous and cognitive this study suggests that reflective sketchbooks document the dialogic encounters of students whilst also providing a material space that can itself become a form of dialogic space for critical reflection. The main findings of the study outline critical ways in which preservice teachers transform theoretical inputs into individual expressions as well as conceptualise theory in relation to lived experience.